On the margins of Utopia: one more look at Mughal painting - Juneja, Monica (The medieval history journal, 2001)
Can a notion of 'utopia' be recovered within a pre-modern, non-European cultural setting, that of the Mughal court? This paper looks for the articulation of this topos as a discursive practice within the spaces of visual representation. It argues that utopia was not conceptualised as an unattainable vision projected onto the future, rather it repre sented an ideal located in the present, one which constituted the present, for time itself was no longer imagined as structured in linear progression. Painted images have been explored as the location of a 'lieu idéologique', and at the same time as spaces from where the persuasive force of ideal visions could be undermined.